Metaphor in communication: the distribution of potentially deliberate metaphor across register and word class. Issue 3 (November 2019) - Reijnierse, W. Gudrun; Burgers, Christian; Krennmayr, Tina; Steen, Gerard J.
Abstract : There is renewed interest in the special role that metaphor can have in its communicative status as metaphor between language users. This paper investigates the occurrence of such deliberate metaphors in comparison with non-deliberate metaphors. To this end, a corpus of 24, 762 metaphors was analysed for the presence of potentially deliberate ( versus non-deliberate) metaphor use across registers and word classes. Results show that 4.36 percent of metaphors in the corpus are identified as potentially deliberate metaphors. News and fiction contain significantly more potentially deliberate metaphors, while academic texts and conversations exhibit significantly fewer potentially deliberate metaphors than expected. Moreover, nouns and adjectives are used relatively more frequently as potentially deliberate metaphors, while adverbs, verbs and prepositions are used relatively less frequently as potentially deliberate metaphors. These results can be explained by referring to the overall communicative properties of the registers concerned, as well as to the role of the different word classes in those registers.